snR30/U17 Small Nucleolar Ribonucleoprotein: A Critical Player during Ribosome Biogenesis - Timothy John Vos; Ute Kothe (Cells, 2020)
The small nucleolar RNA snR30 (U17 in humans) plays a unique role during ribosome synthesis. Unlike most members of the H/ACA class of guide RNAs, the small nucleolar ribonucleoprotein (snoRNP) complex assembled on snR30 does not direct pseudouridylation of ribosomal RNA (rRNA), but instead snR30 is critical for 18S rRNA processing during formation of the small subunit (SSU) of the ribosome. Specifically, snR30 is essential for three pre-rRNA cleavages at the A0/01, A1/1, and A2/2a sites in yeast and humans, respectively. Accordingly, snR30 is the only essential H/ACA guide RNA in yeast. Here, we summarize our current knowledge about the interactions and functions of snR30, discuss what remains to be elucidated, and present two non-exclusive hypotheses on the possible molecular function of snR30 during ribosome biogenesis. First, snR30 might be responsible for recruiting other proteins including endonucleases to the SSU processome. Second, snR30 may contribute to the refolding of pre-rRNA into a required conformation that serves as a checkpoint during ribosome biogenesis facilitating pre-rRNA cleavage. In both scenarios, the snR30 snoRNP may have scaffolding and RNA chaperoning activity. In conclusion, the snR30 snoRNP is a crucial player with an unknown molecular mechanism during ribosome synthesis, posing many interesting future research questions.